Effect of nitrogen vacancies on the growth, dislocation structure, and decomposition of single crystal epitaxial (Ti1-xAlx)Ny thin films. (15th January 2021) - Calamba, K.M.; Salamania, J.; Jõesaar, M.P. Johansson; Johnson, L.J.S.; Boyd, R.; Pierson, J.F.; Sortica, M.A.; Primetzhofer, D.; Odén, M.
Abstract: The effect of varying nitrogen vacancies on the growth, microstructure, spinodal decomposition and hardness values of predominantly single crystal cubic phase c-(Ti1-x Alx )Ny films was investigated. Epitaxial c-(Ti1−x Alx )Ny films with y = 0.67, 0.79, and 0.92 were grown on MgO(001) and MgO(111) substrates by magnetron sputter deposition. High N vacancy c-(Ti1−x Alx )N0.67 films deposited on MgO(111) contained coherently oriented w-(0001) structures while segregated conical structures were observed on the films grown on MgO(001). High resolution STEM images revealed that the N-deficient growth conditions induced segregation with small compositional fluctuations that increase with the number of N vacancies. Similarly, strain map analysis of the epitaxial c-(Ti1−x Alx )Ny (001) and (111) films show fluctuations in strain concentration that scales with the number of N vacancies and increases during annealing. The spinodal decomposition coarsening rate of the epitaxial c-(Ti1−x Alx )Ny films was observed to increase with decreasing N vacancies. Nanoindentation showed decreasing trends in hardness of the as-deposited films as the N vacancies increase. Isothermal post-anneal at 1100 °C in vacuum for 120 min revealed a continuation in the increase in hardness for the film with the largest number of N vacancies (y = 0.67) while the hardness decreased for the films with y = 0.79 and 0.92. These results suggest that nitrogen-deficient depositions of c-(Ti1-x Alx )Ny films help to promote a self-organized phase segregation, while higher N vacancies generally increase the coherency strain which delays the coarsening process and can influence the hardness at high temperatures. Graphical Abstract: Image, graphical abstract